A mutational hotspot in AMOTL1 defines a new syndrome of orofacial clefting, cardiac anomalies, and tall stature. Issue 5 (7th February 2023) - Strong, Alanna; Rao, Soumya; von Hardenberg, Sandra; Li, Dong; Cox, Liza L.; Lee, Paul C.; Zhang, Li Q.; Awotoye, Waheed; Diamond, Tamir; Gold, Jessica; Gooch, Catherine; Gowans, Lord Jephthah Joojo; et al.
Abstract: AMOTL1 encodes angiomotin‐like protein 1, an actin‐binding protein that regulates cell polarity, adhesion, and migration. The role of AMOTL1 in human disease is equivocal. We report a large cohort of individuals harboring heterozygous AMOTL1 variants and define a core phenotype of orofacial clefting, congenital heart disease, tall stature, auricular anomalies, and gastrointestinal manifestations in individuals with variants in AMOTL1 affecting amino acids 157–161, a functionally undefined but highly conserved region. Three individuals with AMOTL1 variants outside this region are also described who had variable presentations with orofacial clefting and multi‐organ disease. Our case cohort suggests that heterozygous missense variants in AMOTL1, most commonly affecting amino acid residues 157–161, define a new orofacial clefting syndrome, and indicates an important functional role for this undefined region.